Pengaruh Persepsi Konsumen Tentang Etika Pengecer Online Terhadap Loyalitas Dengan Karakteristik Individual Sebagai Variabel Moderasi - Dita Wahyunita; Sri Wahyuni Astuti (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2015)
The objectives of this study are to examine the impact of consumers' perceptions regarding the ethics of online retailers (CPEOR) on loyalty and to understand the moderating influence of individual characteristics in consumers' perceptions regarding the ethics of online retailers on loyalty. The CPEOR scale includes security, privacy, non-deception and fulfillment/reliability while the individual characteristics comprise vertical individualism characteristcs and horizontal individualism characteristics. The sample was collected by accidental sampling technic with the total of 200 respondents whom experiencing shopping online within the last three months. The research methods that this study uses are the simple linear regression which examines the impact of consumers' perceptions regarding the ethics of online retailers on loyalty and moderated regression analysis (MRA) which examines the moderating influence of individual characteristics in consumers' perceptions regarding the ethics of online retailers on loyalty. Also, this study has got two hypotheses and the result indicates that consumers' perceptions regarding the ethics of online retailers significantly affects loyalty. Study also found that individual characteristics does moderating consumers' perceptions regarding the ethics of online retailers on loyalty.